Gestão de segurança no trabalho na logística de distribuição de bebidas, aplicada à ISO 45001 - Vianna, Meirielle de Souza (2025)
The research addressed workplace safety management in the beverage distribution logistics sector, highlighting the application of the ISO 45001 standard as a tool for risk reduction and improvement of occupational conditions. The topic was grounded in the growing need for organizations to align their practices with international standards, promoting a safe and healthy environment for workers. In this context, the logistics sector presents specific challenges, such as exposure to repetitive efforts, noise, vibrations, load handling, and adverse environmental conditions. The overall objective of the study was to analyze how the implementation of ISO 45001 guidelines can contribute to the efficient management of health and safety at work, focusing on companies in the beverage distribution logistics sector. The adopted methodology consisted of a Case Study: Verification of compliance with the requirements of the ISO 45001:2018 standard for improving occupational health and safety management. This was based on the analysis of studies published between 2021 and 2025, located in databases such as Lilacs, Periódicos Capes, Google Scholar, and Scielo. The results demonstrated that the application of the ISO 45001 standard, combined with the use of the PDCA cycle, continuous training, and monitoring of performance indicators, promotes risk reduction and productivity improvement. The conclusions reinforce the relevance of integrated practices to ensure safety and strengthen organizational sustainability in the logistics sector. The study contributes both theoretically and practically, offering applicable guidelines for organizations seeking to align with best practices in occupational health and safety.